Influence of the Imposed Parameters on XRD Patterns of Electrochemically Top-Down Obtained Nanoporous Al2O3 on Al1050 Alloy. Issue 1 (June 2020) - Basliu, V; Benea, L; Simionescu, N
Abstract: 1050 Aluminum alloy samples polished electrochemically in solution of 15% Na2 CO3 and 5% Na3 PO4 were subjected to the anodic oxidation process in an acid electrolyte, of 1 M H2 SO4 to which 1 g / L Al2 (SO4 )3 × 18 H2 O was added for the formation on their active surfaces of aluminum oxide nanoporous layers by top-down nanotechnology method. The applied parameters during the anodic oxidation processes were varied in order to obtain the most uniform aluminum oxide nanoporous layers. Thus the potential was varied between 1 V and 25 V, the duration of the oxidation processes was between 10 minutes and 48 minutes and the stirring rate of the electrolyte was between 0 and 700 rotations per minute. The formation of nanoporous layers of aluminum oxide was observed when the applied potential was between 15 V and 21 V, the duration of the anodic oxidation process was varied between 25 and 45 minutes and the stirring rate of the electrolyte was between 0 and 500 rpm. Too low duration and / or too low potential caused an electrochemical polishing phenomenon to occur and the imposition of too high potential caused dissolution of the alloy substrate. Also, the use of a dynamic electrolyte regime produced a homogenization of the electrolyte temperature during the anodic oxidation processes and the growth of the aluminum oxide nanoporous film is slowed down. XRD diffractogram analysis reveals an enhancement in peak intensity correspondent to aluminum oxide concomitantly with a reduction in peak intensity of metallic aluminum for aluminum nanoporous oxide layers in comparison to the surface of polished Al1050 electrochemically.